2015
DOI: 10.1155/2015/316745
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Hypoxia-InduciblemiRNA-210in Patients with Lung Adenocarcinoma

Abstract: Objective. The aim of this study was to investigate the prognostic value of MicroRNA-210 (miR-210) expression in patients with non-small-cell lung cancer (NSCLC). Methods. We examined the miR-210 expression of samples of 80 patients, who underwent surgical resection at Fukushima Medical University from 2004 to 2007, by using quantitative RT-PCR. The relationship between miR-210 expression and clinicopathological factors as well as histological subtype was statistically analyzed. Results. miR-210 expression sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…This result was consistent with previous findings in which miR-210 levels were increased in lung cancer patients (34)(35)(36)(37). MiR-210 levels expression also was a prognostic factor for survival of lung cancer patients (38). However, the mechanism of miR-210 upregulation has not been completely clear.…”
Section: Discussionsupporting
confidence: 92%
“…This result was consistent with previous findings in which miR-210 levels were increased in lung cancer patients (34)(35)(36)(37). MiR-210 levels expression also was a prognostic factor for survival of lung cancer patients (38). However, the mechanism of miR-210 upregulation has not been completely clear.…”
Section: Discussionsupporting
confidence: 92%
“…There were a total of 2 GEO datasets and 4 public studies [35, 41-43], as well as our own RT-qPCR results with an overall number of 396 patients included in this meta-analysis (Table 5). A fixed model was selected for estimation as no significantly high heterogeneity was observed.…”
Section: Resultsmentioning
confidence: 99%
“…VEGF can contribute to tumorigenesis, by promoting angiogenesis and enhancing the blood supply (35). Moreover, miR-210 has been reported to be the most highly induced miRNA in hypoxic cells (36), and hypoxia reduces the radiosensitivity of tumor cells both in vitro and in vivo (37). Previous studies have reported that some miRNAs can regulate the DNA damage response to radiation and participate in DNA repair pathways (38,39), but the mechanisms involved in radioresistance, angiogenesis, apoptosis, cell cycle control and DNA damage/repair are still unknown.…”
Section: Discussionmentioning
confidence: 99%